2015 Updated Method Guideline for Systematic Reviews in the Cochrane Back and Neck Group. Issue 21 (November 2015) - Furlan, Andrea D.; Malmivaara, Antti; Chou, Roger; Maher, Chris G.; Deyo, Rick A.; Schoene, Mark; Bronfort, Gert; van Tulder, Maurits W.
Abstract : Study Design: Method guideline for systematic reviews of trials of interventions for neck and back pain, and related spinal disorders. Objective: To help authors design, conduct, and report systematic reviews of trials in this field. Summary of Background Data: In 1997, the Cochrane Back Review Group editorial board published the Method Guideline for Systematic Reviews, which was updated in 2003 and in 2009. Since then, new methodological evidence has emerged and standards have changed, therefore it was clear that revisions were needed to the 2009 guideline. In May 2015 the group changed its name to Cochrane Back and Neck. Methods: The editorial board met in September 2014 to review the relevant new methodological evidence and determine how it should be incorporated. Members of the advisory board were consulted. Based on the feedback received, an updated method guideline was prepared and approved by the editorial board. Results: We have updated recommendations in 7 categories: objectives, literature search, selection criteria, risk of bias assessment, data extraction, data analysis, and reporting of results and conclusions. Each category is classified into minimum criteria (mandatory) and further guidance (optional). This update also includes some new guidance for preparation of summary of finding tables and for conducting nonintervention reviews. Conclusion: Citations of previous versions of the method guideline in published scientific articles (1193 in total) suggest that others may find this guideline useful to plan, conduct, or evaluate systematic reviews in the field of back and neck pain, and spinal disorders. Level of Evidence: N/A Abstract : Supplemental Digital Content is available in the text